Set Up and Calibration of a Spatial Tool for Simulating River Discharge of Western Java in Recent Decades: Preliminary Results and Assessments - Poerbandono, Poerbandono; Ward, Philip J.; Julian, Miga M. (Journal of Engineering and Technological Sciences, 2009)
This  paper  discusses  a  study  of  the  application  of  global  spatiotemporal climate datasets and the hydrological model STREAM   (Spatial Tools for River Basin Environmental Analysis and Management Options). In the study, set up and calibration  of STREAM for  the reconstruction of monthly discharge for several locations in the western part of Java, Indonesia, for the period 1983 -2002 are carried out. The set up includes the preparation of monthly precipitation and temperature datasets, a digital elevation model of the domain being studied, and maps of land cover and soil water holding capacity. Discharge observations from  six  stations  located  mostly  in  the  upper  parts  of  major  watersheds  in  the domain  are  used  to  calibrate  the  model  by  comparing  simulated  and  observed discharge variables. The model performs reasonably well.  Comparison  between computed and observed mean monthly discharges yield correlation coefficients ranging from 0.72 to 0.93. The  computed mean annual discharge in five out of six  observation  stations  ranges  between  -8  and  5%  with  respect  to  the  mean annual  observed  discharge.  This  study  offers  a  tool  which  can  be  used  for reconstructing historical discharge